2006
DOI: 10.1182/blood-2006-05-022772
|View full text |Cite
|
Sign up to set email alerts
|

Preformed antibody, not primed T cells, is the initial and major barrier to bone marrow engraftment in allosensitized recipients

Abstract: Multiply-transfused individuals are at higher risk for BM rejection. We show that whereas allosensitization resulted in the priming of both cellular and humoral immunity, preformed antibody was the major barrier to engraftment. The generation of cross-reactive alloantibody led to rejection of BM of a different MHC-disparate strain. Imaging studies indicated that antibody-mediated rejection was very rapid (< 3 hours) in primed recipients, while T-cell-mediated rejection in nonprimed mice took more than 6 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 32 publications
3
92
1
Order By: Relevance
“…Immune rejection mediated by residual cellular immunity 1,2 or humoral immunity, 3,4 defects of the host BM microenvironment 5 and viral infections 6 are the main factors presumed to be involved in the occurrence of this complication. As immune rejection occurs as a result of the balance between residual host immunity and graft-derived immunity, the use of non-myeloablative or reduced-intensity conditioning (RIC), 7 T-cell depletion from the graft, 8 low numbers of infused progenitor cells 9,10 and immunological disparity (that is, HLA mismatch) 11 between the host and donor are known to increase the risk of graft failure.…”
Section: Introductionmentioning
confidence: 99%
“…Immune rejection mediated by residual cellular immunity 1,2 or humoral immunity, 3,4 defects of the host BM microenvironment 5 and viral infections 6 are the main factors presumed to be involved in the occurrence of this complication. As immune rejection occurs as a result of the balance between residual host immunity and graft-derived immunity, the use of non-myeloablative or reduced-intensity conditioning (RIC), 7 T-cell depletion from the graft, 8 low numbers of infused progenitor cells 9,10 and immunological disparity (that is, HLA mismatch) 11 between the host and donor are known to increase the risk of graft failure.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In patients receiving major HLA-Ag mismatched allo-SCT, a positive crossmatch has been significantly correlated to increased risk for graft failure and inferior survival as compared with patients transplanted against a negative crossmatch. 9,10 Taken together, on the basis of the above-mentioned publications, we have on a regular basis performed cytotoxic crossmatches in allo-SCT patients before transplantation since 2000.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, recent data from mouse models indicate that the presence of preformed donor-reactive Abs is a dominant barrier for BM engraftment in allosensitized recipients. 7,8 In contrast to organ transplantation, data on the clinical outcome after allo-SCT across a positive crossmatch are scarce. Previous work by Anasetti et al 9 showed that patients with a positive crossmatch had a significantly increased risk of rejection compared with patients with a negative crossmatch.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent with early reports that the majority of hematopoietic progenitor cells co-express HLA-DR 45,46 and that CD4 + T cells recognizing mismatched HLA-DR Ag can be associated with graft failure. 47 Recently, some animal studies suggest that humoral immunity is the major barrier to engraftment, 48,49 although cellular immunity has been recognized as the primary mechanism of rejection. 7 In this study, we could not determine whether humoral or cellular immunity would be a dominant barrier to engraftment.…”
Section: Discussionmentioning
confidence: 99%